Sodium overload due to a persistent current that attenuates the arrhythmogenic potential of a novel LQT3 mutation - Moreau, Adrien; Krahn, Andrew D.; Gosselin-Badaroudine, Pascal; Klein, George J.; Christé, Georges; Vincent, Yohann; Boutjdir, Mohamed; Chahine, Mohamed (Frontiers in Pharmacology, 2013)
Long QT syndrome (LQTS) is a congenital abnormality of cardiac repolarization that manifests as a prolonged QT interval on 12-lead electrocardiograms. The syndrome may lead to syncope and sudden death from ventricular tachyarrhythmias known as torsades de pointes. An increased persistent Na+ current is known to cause a Ca2+ overload in case of ischemia for example. Such increased Na+ persistent current is also usually associated to the LQT3 syndrome. The purpose of this study was to investigate the pathological consequences of a novel mutation in a family affected by LQTS. The impact of biophysical defects on cellular homeostasis are also investigated. Genomic DNA was extracted from blood samples, and a combination of PCR and DNA sequencing of several LQTS-linked genes was used to identify mutations. The mutation was reproduced in vitro and was characterized using the patch clamp technique and in silico quantitative analysis. A novel mutation (Q1476R) was identified on the SCN5A gene encoding the cardiac Na+ channel. Cells expressing the Q1476R mutation exhibited biophysical alterations, including a shift of SS inactivation and a significant increase in the persistent Na+ current. The in silico analysis confirmed the arrhythmogenic character of the Q1476R mutation. It further revealed that the increase in persistent Na+ current causes a frequency-dependent Na+ overload in cardiomyocytes co-expressing WT and mutant Nav1.5 channels, that, in turn, exerts a moderating effect on the lengthening of the action potential duration caused by the mutation. The Q1476R mutation in SCN5A results in a three-fold increase in the window current and a persistent inward Na+ current. These biophysical defects may expose the carrier of the mutation to arrhythmias that occur preferentially in the patient at rest or during tachycardia. However, the Na+ overload counterbalances the gain-of-function of the mutation and is beneficial in that it prevents severe arrhythmias at intermediate he